Chemoenzymatic synthesis of the enantiomers of desoxymuscarine - P. Conti; C. Dallanoce; M. De Amici; C. De Micheli; G. Carrea; F. Zambianchi (Tetrahedron: Asymmetry, 1998)
Two different chemoenzymatic approaches allowed the preparation of the enantiomers of desoxymuscarine 5, a muscarinic receptor agonist. Transesterification of racemic 5-hexen-2-ol 7 with vinyl butyrate under the catalysis of Candida antarctica B lipase was the key step for the preparation of (-)-5 (2R,5R). On the other hand, lipase PS-catalyzed hydrolysis of iodo butyrate (+/-)-14 was utilized to obtain (+)-5 (2S,5S). Both enantiomers were prepared with enantiomeric excesses higher than 98%. (C) 1998 Elsevier Science Ltd. All rights reserved.